Upaya Internalisasi Nilai Pendidikan Agama Islam dalam Peningkatan Produktivitas Akademik Peserta Didik - Ihsan, Muh (Yayasan Letiges Konsultan Sosial, 2023)
The potential of students is one of the gifts and creations of Allah SWT which is very unique compared to His other creations. Its uniqueness can be seen in the ability of these students to change themselves in a more advanced and developing direction, in line with their growth and development. The ability to change students themselves does not take place immediately, but many things that influence and play the most role are the family environment and the world of education and their association in the community. The purpose of this research is to answer these problems in an effort to internalize the value of Islamic religious education in increasing student productivity. The method used in this research is literature review. Sources of data are in the form of books, journals, government regulatory documents or other relevant references. The data is then analyzed using content analysis techniques. The results of this study state that the value internalization approach is related to the process of actualizing, instilling normative values that determine behavior according to academic goals. Meanwhile, academic productivity is related to works that are made independently in the form of innovative works or finished goods. The concoction found is a display of behavior based on scientific values and independence in academic production.